Complete remission of giant malignant phyllodes tumor with lung metastasis: A case report - Moon, So Hyang (Medicine (Baltimore), 2019)
RATIONALE: Malignant phyllodes tumors are rare breast neoplasms that are associated with a 6.2% to 25% incidence rate of distant metastasis; the lung is the most common metastatic site. To date, there is no consensus regarding the treatment of metastatic malignant phyllodes breast tumors. PATIENT CONCERN: A 48-year-old woman was admitted into the breast clinic for a rapidly growing right breast tumor that was first noticed 1 month prior. DIAGNOSIS: Core needle biopsy revealed a malignant phyllodes tumor. A chest computed tomography and positron emission tomography/CT showed metastatic lymph nodes that appeared to have spread to the right axilla, as well as multiple solitary pulmonary nodules in the right lung. Fine needle aspiration on the axillary lymph node confirmed metastasis. INTERVENTIONS: A right mastectomy with axillary lymph node dissection was conducted and a thoracoabdominal flap and a split thickness skin graft were performed for the skin defect. Palliative chemotherapy with doxorubicin plus ifosfamide was performed. OUTCOMES: An examination conducted 3 years postsurgery showed no signs of recurrence, and the patient's overall health status was satisfactory. LESSONS: As standard treatment guidelines for metastatic malignant phyllodes tumors are lacking, we opted for the aforementioned aggressive treatments that resulted in complete remission of the lung metastasis. Therefore, aggressive treatment, whenever possible, is warranted.